Dietary protein for athletes: From requirements to optimum adaptation - Phillips, S. M.; Van Loon, L. J. C. (Journal of Sports Sciences, 2011)
Opinion on the role of protein in promoting athletic performance is divided along the lines of how much aerobic-based versus resistance-based activity the athlete undertakes. Athletes seeking to gain muscle mass and strength are likely to consume higher amounts of dietary protein than their endurance-trained counterparts. The main belief behind the large quantities of dietary protein consumption in resistance-trained athletes is that it is needed to generate more muscle protein. Athletes may require protein for more than just alleviation of the risk for deficiency, inherent in the dietary guidelines, but also to aid in an elevated level of functioning and possibly adaptation to the exercise stimulus. It does appear, however, that there is a good rationale for recommending to athletes protein intakes that are higher than the RDA. Our consensus opinion is that leucine, and possibly the other branched-chain amino acids, occupy a position of prominence in stimulating muscle protein synthesis; that protein intakes in the range of 1.3-1.8 g/kg .day consumed as 3-4 isonitrogenous meals will maximize muscle protein synthesis. These recommendations may also be dependent on training status: experienced athletes would require less, while more protein should be consumed during periods of high frequency/intensity training. Elevated protein consumption, as high as 1.8-2.0 g/kg·day depending on the caloric deficit, may be advantageous in preventing lean mass losses during periods of energy restriction to promote fat loss.